Perbedaan kadar kolesterol low density lipoprotein (LDL) pada diabetes mellitus tipe 2 dengan hipertensi serta tanpa hipertensi di RSUP Sanglah Denpasar, Bali - Stephanie Inge Wijanarko; Sianny Herawati; Anak Agung Ngurah Subawa (E-Jurnal Medika Udayana, 2018)
Diabetes Mellitus was a disease with high blood sugar levels that allows the patient to an increase in blood pressure. Increased blood pressure itself is suspected because of the increased levels of LDL. This study aims to prove whether there is a difference between the levels of LDL in patients of DM type 2 with hypertension and without hypertension. The study was cross sectional analytic to determine differences in levels of LDL cholesterol in DM type 2 with or without hypertension. . The mean levels of LDL in patients with DM type 2 with hypertension (n=28) is 127.72 ± 73.7 (41-435) while the mean LDL levels in patients with DM type 2 without hypertension (n=25) was 73.70 ± 27.47 (6.46 - 120) with p = 0.0001. From these results it can be concluded that, there were significant differences for average levels of LDL patients of DM type 2 with hypertension and patients with DM type 2 without hypertension. Keywords: Diabetes Mellitus, Hypertension, LDL, Sanglah Hospital